Analisis sikap pustakawan dalam melayani pemustaka berdasarkan kode etik pustakawan di perpustakaan umum kota padang panjang - Redito Afif; Yuldelas Harmi (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
The main problem in this thesis is how the attitude of librarians in serving users is based on the librarian's code of ethics at the Padang Panjang City Public Library. The purpose of this research is to describe the attitude of librarians about Asta Ethics of librarians in providing services to users at the Padang Panjang City Public Library, as well as to describe the perceptions of users of the services provided by librarians at the Padang Panjang City Public Library. Asta ethics are guidelines for librarians to behave and act in accordance with the regulated code of ethics. This type of research is qualitative with a descriptive approach. Data collection techniques through observation, interviews and documentation. Data analysis techniques start from data reduction, data presentation and drawing conclusions. Guarantee the validity of the data in this study using source triangulation. The results of the study show that the attitude of librarians regarding basic ethics in the Padang Panjang Public Library as a whole, all librarians have understood the meaning of basic ethics in general. Asta ethics is important as a rule that must be obeyed and used as a guide in carrying out duties in a professional manner. Asta librarian ethics are eight codes of ethics for librarians in providing library services to the community. The librarian's code of ethics is a moral requirement that librarians should follow and comply with. The role of asta ethics for librarians in providing services to users is very important. As for the user's perception of the attitude of librarians in providing services, librarians have not fully been able to apply ethical standards, as there are still some librarians who show an unfriendly attitude in serving users, speak in a high tone so as to disturb the peace of the user and the lack of librarians in applying thanks to users , even though this is something that is very easy to say to someone. Then the efforts made by the library for the attitude of librarians who are not well received by users are by evaluating performance and improving the quality of its human resources. Suggestions from researchers for librarians at the Padang Panjang City Public Library are that librarians are expected to increase their understanding of librarian ethics and increase their role according to ethical standards in providing services to users.